The Influence of Liquidity, Leverage, and Firm Size on Tax Aggressiveness (Case Study on Mining Companies Listed on the Indonesia Stock Exchange) - Ramadanti; Seralurin, Yohanes C.; Patma, Kurniawan; Pattiasina, Victor (Yayasan Ilomata, 2024)
This study aims to examine and provide empirical evidence on the influence of liquidity, leverage, and firm size on tax aggressiveness. The population in this study consists of mining companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling method used in this study is purposive sampling. Data collection methods include literature review and documentation. Descriptive statistical analysis and Structural Equation Modeling (SEM) based on components or variances, known as Partial Least Square (PLS), are used as methods to analyze the data. The software used in this study is SmartPLS. The results of this study indicate that liquidity does not affect tax aggressiveness, leverage does not affect tax aggressiveness, and firm size has a negative and significant effect on tax aggressiveness.